Genetically Encoded Calcium Indicators and Astrocyte Calcium Microdomains. (June 2013) - Tong, Xiaoping; Shigetomi, Eiji; Looger, Loren L.; Khakh, Baljit S.
The discovery of intracellular Ca 2+ signals within astrocytes has changed our view of how these ubiquitous cells contribute to brain function. Classically thought merely to serve supportive functions, astrocytes are increasingly thought to respond to, and regulate, neurons. The use of organic Ca 2+ indicator dyes such as Fluo-4 and Fura-2 has proved instrumental in the study of astrocyte physiology. However, progress has recently been accelerated by the use of cytosolic and membrane targeted genetically encoded calcium indicators (GECIs). Herein, we review these recent findings, discuss why studying astrocyte Ca 2+ signals is important to understand brain function, and summarize work that led to the discovery of TRPA1 channel-mediated near-membrane Ca 2+ signals in astrocytes and their indirect neuromodulatory roles at inhibitory synapses in the CA1 stratum radiatum region of the hippocampus. We suggest that the use of membrane-targeted and cytosolic GECIs holds great promise to explore the diversity of Ca 2+ signals within single astrocytes and also to study diversity of function for astrocytes in different parts of the brain.